2016
DOI: 10.1021/acs.jafc.6b01903
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Fatty Acid Profile and Phospholipid Molecular Species Composition of Human Erythrocyte Membranes after Hybrid Palm and Extra Virgin Olive Oil Supplementation

Abstract: This work aims to evaluate and compare, for the first time, the effects of extra virgin olive oil (EVOO) and hybrid palm oil (HPO) supplementation on the fatty acid profile and phospholipid (PL) molecular species composition of human erythrocyte membranes. Results supported the effectiveness of both HPO and EVOO supplementation (3 months, 25 mL/day) in decreasing the lipophilic index of erythrocytes with no significant differences between HPO and EVOO groups at month 3. On the other hand, the novel and rapid u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 44 publications
3
18
0
Order By: Relevance
“…Whatever the form of consumption, we see a variation of cholesterol in the same direction with a tendency to hypocholesterolemia after four weeks of dieting, with no significant difference. Our results are consistent with those of Pacetti et al [14] who showed stabilization or even a decrease in the total cholesterol among patient's consumers of palm oil. Similarly, Ebong [16] demonstrated the influence of palm oil in lowering the total cholesterol.…”
Section: Lipid and Lipoprotein Parameters Variationssupporting
confidence: 93%
See 2 more Smart Citations
“…Whatever the form of consumption, we see a variation of cholesterol in the same direction with a tendency to hypocholesterolemia after four weeks of dieting, with no significant difference. Our results are consistent with those of Pacetti et al [14] who showed stabilization or even a decrease in the total cholesterol among patient's consumers of palm oil. Similarly, Ebong [16] demonstrated the influence of palm oil in lowering the total cholesterol.…”
Section: Lipid and Lipoprotein Parameters Variationssupporting
confidence: 93%
“…Onyeali et al [29] pointed out a significant reduction in triglycerides, as well as Zhang et al [31], Arenceta et al [33] who demonstrated the influence of palm oil consumption in the reduction or normalization of serum triglycerides. The work of Sundram [14] and Ebong [16] had also shown that palm oil consumption does not significantly influenced triglycerides subjects.…”
Section: Relationship Between Triglyceridemia and Consumption Or Non mentioning
confidence: 99%
See 1 more Smart Citation
“…However, in those feeding studies, the amount of high-oleic oil consumed was much higher (>10 times) than that in our study, which was a supplement trial without experimentally altering participants’ usual diet. A 3-month extra virgin olive oil (>70% oleic acid) supplementation trial showed change of red blood cell fatty acid profile [31]; however, the dose of 25ml oil per day was a little over 4 times that used in our study.…”
Section: Discussionmentioning
confidence: 57%
“…Further, several studies have reported the favorable impacts of HPO on plasma lipids related to cardiovascular diseases by highlighting the relationship between oleic acid and the decrease in low-density lipoproteins (or "bad cholesterol") in the blood Mattson & Grundy, 1985;Ojeda et al, 2017). Therefore, PS could be replaced totally or partially by HPS to achieve dietary substitution of saturated palmitic acid by monounsaturated oleic acid of the hybrid palm, thus providing a mix with greater health benefits Ojeda et al, 2017;Pacetti et al, 2016). Furthermore, same fatty acid profiles were obtained for the mixtures after enzymatic interesterification.…”
Section: Compositional Analysismentioning
confidence: 99%